Management and outcome of acute and recurrent pericarditis during pregnancy. (25th November 2020) - Lotan, D; Wasserstrum, Y; Itelman, E; Nir-Simchen, M; Arad, M; Kuperstein, R
Abstract: Background: Pericarditis in pregnancy is uncommon. Treatment options, including NSAIDs and long term gluco-corticosteroids (CS) have extensive side-effects, while data on the use of Colchicine in pregnant women who suffer from pericarditis is limited. Objective: To evaluate the management and outcome of active pericarditis during pregnancy in both acute (AP) and recurrent pericarditis (RP) patients. Methods and results: Twelve pregnant women (14 pregnancies) with active pericarditis were followed prospectively in our cardiology-pregnancy clinic; 6 with AP and 8 with RP. Etiology: 11 idiopathic, 2 post-pericardiotomy syndrome and 1 Q fever. Maternal age on presentation was 27±4y vs. 33±3y in RP vs AP respectively. Average gestational age upon diagnosis was lower in RP than in AP (18 weeks, range 6–30 vs 26 weeks, range 5–35). In the RP group, 7/8 women (87%) were treated with CS compared with 2/6 women (33%) in the AP group; 3 women in RP group (37%) failed to respond to subsequent treatment with azathioprine and 1 patient was treated successfully with Anakinra. Colchicine was prescribed in 13/14 (93%) of pregnancies, average colchicine exposure during pregnancy was 25±15 weeks. Recurrence during pregnancy: 6/8 (75%) of RP; 2/6 (33%) of the AP, all of them on CS. All pregnancies culminated in a live birth with a mean gestational age on delivery of 37±1.4 weeks. Average birthweight was 3267±507 grams. There were no fetal anomalies or developmental delays after a mean follow-up of 2.7 years. All newborns and maternal outcomes were normal. On long term follow-up after delivery RP patients treated with colchicine developed less recurrences. Conclusion: Active pericarditis is associated with a high recurrence rate during pregnancy despite treatment with CS. Colchicine use in pregnant women with active pericarditis appears to be safe. Funding Acknowledgement: Type of funding source: None